THE ROLE OF FOREIGN INVESTMENT IN IMPROVING THE LOCAL ECONOMY: CASE STUDIES IN SOUTHEAST ASIA - Yunior Pasagi; Ahmad Solihin; Anita Kusuma Dewi (Adisam Publisher, 2025)
Foreign direct investment (FDI) has been recognized as an important catalyst in advancing the economies of developing countries, especially in the Southeast Asia region. This research aims to analyze the impact that foreign investment has on the local economy in Southeast Asia, with a focus on economic growth, job creation, technology transfer, and development of key sectors. The research results show that foreign investment has a significant role in accelerating the economic development process, through various channels such as increasing employment opportunities, improving the quality of human resources, as well as technological innovation and infrastructure development. Foreign investment also plays a role in the economic integration of Southeast Asian countries into the global economy, enabling access to wider export markets and supporting the country in facing international competition. However, this research also identifies several challenges, including regional disparities in attracting FDI, the risk of a race to the bottom due to competition in providing incentives to investors, and the need for improvements in aspects of governance and transparency to ensure that foreign investment has an inclusive and sustainable positive impact for the local economy.